THE ROLE OF PENITENTIARY OFFICERS IN INMATE REHABILITATION - Yoan Barbara Runtunuwu; Wenly R. J. Lolong (Awang Long Law Review, 2026)
This study aims to analyze the role of the penitentiary system in supporting the effectiveness of inmate rehabilitation and its contribution to reducing recidivism rates and ensuring successful social reintegration. The method used is normative juridical legal research, which involves examining statutory regulations, legal doctrines, academic literature, and relevant court decisions. The approaches employed include the statutory approach, conceptual approach, case approach, and historical approach, all of which reinforce the analysis of regulatory developments and the application of norms related to the penitentiary system and inmate rehabilitation. The research findings indicate that the penitentiary plays a strategic role in reshaping inmate behavior through the implementation of development programs that include education, skills training, counseling, mental development, and social support. The success of the rehabilitation process is highly influenced by the ability of correctional institutions to integrate various aspects of guidance, supervision, and social reintegration in a synergistic manner. Additionally, the study finds that correctional institutions hold a vital position within the integrated criminal justice system, as they ensure the protection of inmates’ rights throughout the legal process. Overall, this study concludes that the effectiveness of the penitentiary system is determined not only by normative aspects but also by the commitment to implementation at the operational level. The success of correctional efforts is reflected in lower recidivism rates and the increased capacity of former inmates to return as productive and responsible members of society after serving their sentences.